Character Formation in Elementary Schools: Empirical Foundation for the AFK Strategy Based on Lickona’s Framework - Winda Annisha Bertiliya; Bujang Rahman; Muhammad Nurwahidin; Undang Rosidin (Universitas Negeri Malang, 2025)
The growing concern over student behavior, including bullying, lack of empathy, and dishonesty, underscores the inadequacy of current character education practices in Indonesian elementary schools. This study aims to provide an empirical foundation and conceptual justification for a new instructional model—Action–Feeling–Knowing (AFK)—designed to improve character formation. Employing a descriptive qualitative approach, data were collected from ten teachers at SDN 1 Labuhan Ratu through observation instruments aligned with the five core PPK values: religiosity, nationalism, independence, mutual cooperation, and integrity. The results reveal an overall character competency score of 43.98%, with integrity and mutual cooperation being the weakest domains. Qualitative narratives highlight disconnection between moral teaching and real-life application, limited emotional engagement, and inconsistencies between school and home environments. In response, this study proposes the AFK strategy, which begins with student action, followed by emotional reflection and cognitive understanding. Supported by behaviorist, constructivist, and humanist theories, this reversed sequence better aligns with the developmental stage of primary students. A bibliometric analysis using Publish or Perish and VOSviewer confirms the limited scholarly attention to this specific model, reinforcing its originality. The study concludes that AFK holds promise as an actionable, integrated, and developmentally sensitive approach to character education, meriting further research and classroom-based implementation.